Elements of Architectural Design for Oncology Centers and Methodology of Development for Existing Centers - Mostafa Hossin (Journal of Engineering Research - Egypt, 2023)
The research paper reviews the architectural design requirements for specialized tumor centers, which are considered specialized medical care buildings to treat different types of tumors, and the methodology for developing and raising the efficiency of existing medical centers through a case study of two projects to develop existing tumor centers. The research is divided into two main parts. The first section is an analytical study of a set of local and international specifications for designing cancer centers according to the latest technical recommendations. It covers standard dimensions and design requirements, which are a necessary part to know before starting any development work, and compare requirements. The second section discusses the experience of developing and raising the efficiency of two specialized centers in the treatment of oncology, the first is the Jeddah Oncology Center in the Kingdom of Saudi Arabia, as a case study, in which all development work and the operation of all devices in the center are completed in 2017, and the second is the National Cancer Institute in Cairo Where the development work began in 2019, and the research presents the steps of the development process that were followed, and the various design alternatives, an explanation of some of the units that were developed in the center, and this section concludes with a proposed methodology of research for the processes of developing and raising the efficiency of the existing specialized medical care centers, and finally a group of the findings and recommendations.